CURRENT STATE, DYNAMICS, LEVEL OF PAY FOR LABOR AND ITS PRODUCTIVITY IN THE AGRICULTURAL SECTOR - SOKOLOVA, Alla; RATOSHNIUK, Tatiana; KILNITSKA, Olena; ZELINSKA, Antonina (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines the current state of material motivation of agrarian labor in agricultural enterprises of the natural and economic zone of the Western Polissia of Ukraine, and evaluates the dynamics and level of labor remuneration and its productivity. The main directions of labor productivity growth based on the formation and implementation of an effective motivational mechanism in each agrarian formation of the region are outlined. Among the main factors that affect the motivation of work in the agricultural sector: the importance of the availability of human capital; collective nature of work; risky nature of agricultural production; dynamism and complexity of agricultural processes; responsibility for the quality and timeliness of agro-technological operations, etc. The development of the agrarian sector of the Ukrainian economy in the conditions of the European integration perspective requires adequate changes in the system of distribution of the created aggregate product, control, registration, taxation of a significant part of the population’s monetary income and a comprehensively justified policy in the sphere of wages and taxation. Therefore, one of the factors of the strategic development of the agrarian economy is the orientation of production on the European integration path of development based on competitive relations, the activation of targeted efforts of agricultural workers, the development of their creative initiative and entrepreneurship, the search for and involvement of internal reserves in production.